Rounders Game Learning for Class V Mis Bustanul Ulum Badas: A Study Basic Skill Level - Atmam Amir; Chunaifi, Muhammad Aang; Irvan Sir (Education and Talent Development Center Indonesia (ETDC Indonesia), 2022)
Physical education, sports, and health are some of the most popular subjects for elementary school children. In addition, through learning physical education, sports and health, children can learn while playing, because many of the materials taught are related to games. The rounders game is a material in the fifth-grade elementary school learning curriculum. So, research on basic skills in learning the rounders game is very necessary to understand the learning process and the development of students' skills. This research is descriptive research with a survey method that aims to determine the level of basic skills, especially in the rounders game material. The data obtained through the test of practice and practice was analyzed using descriptive statistical techniques in the form of percentages. The instruments used to collect data through skill tests are ball throwing, catching, and hitting ball tests with a validity level of 0.413, with a throwing reliability level of 0.765, a hitting reliability level of 0.723, and a catching reliability level of 0.785. The results of the research on the basic skills of playing rounders are divided into several categories: